2022
DOI: 10.1080/21655979.2022.2083822
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B attenuates membranous nephropathy by activating renal autophagy via microRNA-145-5p/phosphatidylinositol 3-kinase/AKT pathway

Abstract: The abnormal proliferation and inflammatory response of the mesangial cells play a crucial role in the progression of membranous nephropathy (MN). Herein, this study aimed to investigate the therapeutic effect of Salvianolic acid B (SalB) on MN-induced mesangial abnormalities and its underlying mechanisms. MN models were established in cationic bovine serum albumin-induced Sprague-Dawley rats and lipopolysaccharide-induced human mesangial cells (HMCs). Following SalB and microRNA-145-5p antagomir treatment, ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Triptolide cures MN through modifying the P13K/AKT1/mTOR signaling pathway, according to Zhang P. et al [ 35 ] network pharmacology and experimental validation, Heymann nephritis in rats was used by Yin J et al [ 36 ] to show that Tetrandrine cures MN via altering the P13K/AKT signaling pathway. Furthermore, Chen J et al [ 37 ] showed in vitro that Salvianolic acid B reduces MN by triggering renal autophagy via the microRNA-145-5p/P13K/AKT pathway. These findings support the findings of the KEGG pathway enrichment study and show the significance of AKT1 in the occurrence, development, and management of IMN.…”
Section: Discussionmentioning
confidence: 99%
“…Triptolide cures MN through modifying the P13K/AKT1/mTOR signaling pathway, according to Zhang P. et al [ 35 ] network pharmacology and experimental validation, Heymann nephritis in rats was used by Yin J et al [ 36 ] to show that Tetrandrine cures MN via altering the P13K/AKT signaling pathway. Furthermore, Chen J et al [ 37 ] showed in vitro that Salvianolic acid B reduces MN by triggering renal autophagy via the microRNA-145-5p/P13K/AKT pathway. These findings support the findings of the KEGG pathway enrichment study and show the significance of AKT1 in the occurrence, development, and management of IMN.…”
Section: Discussionmentioning
confidence: 99%
“…In rats with cationic calf serum albumin-induced chronic glomerulonephritis, salvianolic acid B can improve renal function by inhibiting inflammation (decreased expression of IL-1β and IL-6), alleviating oxidative stress (decreased MDA levels and increased SOD and GSH activities), and promoting autophagy (decreased p62 expression and increased the LC3 II/LC3 I ratio and Beclin1 expression) [ 119 ]. Salvianolic acid B significantly ameliorated kidney function and pathological changes in rats with cationic bovine serum albumin-induced membranous nephropathy and LPS-induced human mesangial cells by upregulating miR-145-5p to inhibit the PI3K/Akt signaling pathway and by upregulating mesangial cell autophagy, thus reducing cell proliferation and inflammation [ 120 ].…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…Similarly, salvianolic acid B activates renal autophagy by targeting the phosphoinositol-3 kinase (PI3K)/protein kinase B (AKT) pathway through microRNA-145-5p, consequently reducing inflammation and cell proliferation (Chen J et al. 2022 ). Additionally, salvianolate has been found to protect against MGN by inhibiting hypercoagulable states and promoting the expression of Wilms’ tumour protein 1 (WT-1), podocalyxin (PCX) and vascular endothelial growth factor (VEGF) in renal tissue, which ultimately aids in the repair of podocyte injury (Chen W et al.…”
Section: Introductionmentioning
confidence: 99%